Covid-19 research evidence: An international survey exploring views on useful sources, preferred formats, and accessibility - Tomlinson, Eve; De Silva, Debra; Stojanova, Jana; Parker, Roses; Umoquit, Muriah; Lagosky, Stephanie; Schmidt, Bey-Marrié; Head, Karen (Journal of Evidence-Based Healthcare, 2022)
INTRODUCTION: In a pandemic, stakeholders such as policy makers, clinicians, patients, and the public need access to high-quality, timely, relevant research evidence in a format that is understandable and applicable. OBJECTIVES: An online survey was used to determine where a global audience finds research evidence about COVID-19 and how they prefer to keep up to date. METHODS AND MATERIALS: We conducted an online survey of people interested in research in English and Spanish. We used a convenience sample of people visiting websites and social media accounts of Cochrane, an international organisation that collates systematic reviews of research.  RESULTS: 831 people with various roles and locations responded over a short period with little active promotion. Healthcare professionals, members of the public, and policy influencers wanted research evidence to inform decisions about COVID-19. More than half found research evidence from government websites (52%), international organisations (57%), journals (56%), and evidence collation organisations (60%) useful. People wanted research evidence about COVID-19 formats such as lay summaries (60%), online systematic reviews (60%), short summaries with commentaries (51%), and visual summaries (48%). People preferred to be kept up to date about COVID-19 research via email updates and newsletters, tailored to people’s interests (34%), traditional media (13%) and social media (12%). CONCLUSIONS: It was feasible to collect feedback rapidly using a simple online survey. Websites from official organisations were key sources of COVID-19 research evidence. More research is needed on how best to provide evidence that is easy to access and understand.